Phytochemical and bioactivity studies of Callicarpa maingayi K. & G - Mohammed Othman Asiri, Sumayyah (2012)
Callicarpa maingayi, which is known in Malaysia as “tampang besi” belongs to Lamiaceae family. The plants of the genus Callicarpa have been used to treat various ailments, such as malaria, skin cancer, indigestion, dropsy, stomach disorders and rheumatism. The stem bark of Callicarpa maingayi was exhaustively extracted using methanol-water (8:2). The crude extract was successively fractionated using n-hexane, chloroform and ethyl acetate. Separation, isolation and purification of compounds were done using solvent-solvent partitioning and chromatographic techniques such as High Performance Liquid chromatography (HPLC), as well as normal phase, reverse phase and Sephadex LH-20 column chromatography. From the hexane extract, three known compounds were isolated, namely palmitic acid(91), tetracosanoic acid (92) and a mixture of stigmasterol and β-sitosterol (93). The investigation on the chloroform extract led to the isolation of two new naphthoquinone, (+)-callicarpaquinone-A (97), callicarpaquinone-B (96), along with known avicequinone-C (95), which was isolated from the first time from Callicarpa species, and 3β-hydroxy-lup-20(29)-en-28-oic-acid (94). From the ethyl acetate extract, three known compounds (+)-paulownin (98), (-)-wodeshiol (99), which were isolated for the first time from Callicarpa species together with β- sitosterol-β-D-glucopyranoside (100). The extracts and isolated compounds were screened in vitro for anticholinesterase and cytotoxic activities using Ellman's and MTT (3-(4,5-dimethylthiazole-2-yl)-2,5- diphenyltetrazolium bromide) methods. The hexane, chloroform and ethyl acetate extracts were inactive against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with IC50 values of > 100 μM, but were found to exhibit significant cytotoxicity against liver cancer (HepG2) and breast cancer (MCF-7) cell lines with IC50 values ranging from 12.5 to 25.0 μg/mL. The isolated compounds, (+)-callicarpaquinone-A (97), callicarpaquinone-B (96), avicequinone-C (95), (+)-paulownin (98) and (-)-wodeshiol (99) were inactive against AChE with IC50 values of > 100 μM. However, they were active against the MCF-7 breast cancer cell line with IC50 values of 25.0, 1.9, 2.3, 14.0 and 14.0 μM, respectively. The structures of the isolated compounds were elucidated using spectroscopic techniques including UV, IR, MS, 1H NMR, 13C NMR, DEPT, HMBC and1H-1H COSY.